The Effect of Promotion on the Decision to Choose a Higher Education through the Brand Image of Education - Umin Kango; Ari Kartiko; Muhammad Anas Maarif (AL-ISHLAH: Jurnal Pendidikan, 2021)
Increasingly fierce competition from universities in getting new students requires universities to carry out marketing activities well, one of which is through promotion and formation of a good college image to influence the decisions of prospective new students in choosing a university. This research uses quantitative research, which consists of promotion variable (X1) as an exogenous variable, education image (Y1) as intervening variable, and decision to choose university (Y2) as an exogenous variable. This study uses primary data. It is obtained directly from respondents through questionnaires that have been tested for validity and reliability tests for each question item or statement that will be submitted to respondents. Data analysis technique to test the relationship between variables using structural equation modelling (SEM) using AMOS25. The sample of this study was 148 students of the Tarbiyah in an Institute. This study indicates that sales have a significant effect on choosing a college, and the image of education significantly affects college decisions. At the same time, the primary outcome variable can mediate the promotional education image variable on the decision to choose a college.